The latest foundations for the development of production, science and education – 2026 - Chubka, Olha; Donchak, Lеsia; Balyk, Ulyana; Hirna, Olha; Shkvaruk, Dina; Smolinska, Nataliya; Vynnychuk, Roksolana; Boikivska, Halyna; Kharchuk, Viktoriya; Boikivska, Sofiia; Koval, Zoriana; Nakonechna, Taisiia; et al. (Publishing House NES Nová Dubnica s.r.o., 2026)
The collective monograph summarizes modern trends in pedagogical design, interdisciplinary aspects of modern transformational processes in society. The main problems, trends, perspectives and directions of shifts in society as a result of the change of development paradigms are defined and characterized. The didactic and educational aspects of pedagogical design in professional education and higher education are analyzed, and the problems of managing pedagogical design are considered. The objective logic of changing development paradigms as a result of informational, communication and structural changes in society is revealed, which affects the transformation of technical-technological, socio-economic, political-legal, statist, educational and cultural reality, determines a new dimension of modern social processes. The monograph is intended for a wide range of researchers, teachers and students of higher education institutions, heads of educational institutions and organizations, non-profit institutions and business structures, representatives of state and public authorities, all interested in the development of pedagogical design and modern society.